Challenges faced by MSICs operators - Jamaludin, Mariam; Yusof, Zeenat Begam (Association of Malaysian Environment-Behaviour Researchers (AMER), 2017)
Sustainability becomes main management issues for hospitality firms. Big hospitality firms conduct countless attempts to accommodate into the sustainability agenda. However, the small hospitality firms are left behind. The reason is some challenges that are dragging them. Challenges studies regarding big hospitality companies are plenteous. However, studies regarding challenges of MSIC operators are limited in Malaysia. Therefore, the objectives are to identify the challenges and the rankings. This study is applying the quantitative and qualitative approach. The finding shows that lack of green products is the most salient challenges. In conclusion, this study has managed to identify challenges and provide some recommendations.